Enhancing functional motor outcomes in chronic stroke: A systematic review of the growing role of non-invasive brain stimulation - Mirjam Bonanno; Maria Grazia Maggio; Angelo Quartarone; Giovanni Morone; Alessandro Marco De Nunzio; David Militi; Carmela Casella; Svonko Galasso; Rocco Salvatore Calabrò (PLoS ONE, 2025)
Introduction Non-invasive brain stimulation (NIBS) promotes functional recovery by enhancing neuroplasticity and reorganizing brain networks. It is hypothesized that transcranial magnetic stimulation (TMS), repetitive transcranial magnetic stimulation (rTMS), or intermittent θ-burst stimulation (i-TBS) as well as trans direct current stimulation (tDCS) can modulate synaptic connectivity, through magnetic or electric stimuli, directly on the brain area. This systematic review aims to address the lack of comprehensive syntheses focusing on the comparative effectiveness of NIBS techniques, including tDCS, rTMS, and iTBS, on distinct motor domains (upper limb, lower limb, and vocal/swallowing functions) in chronic stroke patients. Evidence acquisition A systematic search was conducted for all peer-reviewed articles published from January 2010 through September 2023, using the following databases: PubMed, Embase, Cochrane Database of Systematic Reviews, PEDro, RehabData, and Web of Science. This systematic review was performed following the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, with a registration number in the Prospective Register of Systematic Reviews (PROSPERO 2023) CRD42023458370. A total of 58 studies were included in the qualitative synthesis: 27 focused on upper limb rehabilitation, 13 on lower limb function, 13 on the combination of NIBS and robotic therapy, and 6 on vocal or swallowing functions. Most studies (78%) were randomized controlled trials. Among the NIBS techniques, tDCS showed stronger evidence for gait and balance recovery, while rTMS appeared more effective for upper limb function. Overall, the majority of studies presented a low risk of bias, although methodological issues such as inadequate randomization or blinding affected the reliability of some findings. Conclusion We have systematically reviewed the literature on the use of NIBS to enhance motor outcomes (upper limb, lower limb, and vocal/swallowing functions) in individuals with chronic stroke. Findings indicate that rTMS demonstrates greater efficacy in improving upper limb motor function, whereas tDCS appears to be more effective in enhancing gait and balance recover.